Feeding management practices and forage utilization in smallholder goat farming in Oransbari District, Papua Barat - Sellau, Ribka H.; Saragih, Evi W; Lekitoo, Marlyn N. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
Smallholder goat production in remote regions of eastern Indonesia still relies mainly on traditional feeding practices that may limit animal performance. This study aimed to describe feed management and forage utilization by smallholder goat farmers in Oransbari District, South Manokwari Regency, West Papua, Indonesia. A descriptive case-study design was applied with 28 purposively selected farmers. Primary data were collected through field observations of available forage, semi-structured interviews on feeding practices, daily weighing of fresh forage offered by growth class, and laboratory analysis of representative forage samples for crude protein, crude fiber, and minerals. Most farmers were of productive age but had low to medium levels of formal education, and feeding decisions were driven mainly by experience and seasonal forage availability rather than by explicit nutritional planning. Adult goats typically received 2–4% of live weight as fresh forage per day, while kids and growers received approximately 1–6%, with rations dominated by Napier grass supplemented with legumes, sweet potato vines, and agricultural by-products. Forage analysis confirmed that the inclusion of legumes substantially increased dietary protein, whereas practices such as wilting and systematic forage conservation were rarely applied. These findings highlight the need for targeted training on nutrition-based rationing, forage conservation, and strategic use of crop residues to improve feed efficiency, animal health, and the sustainability of smallholder goat systems in Oransbari.